Cardioprotective effect of bioflavonoids against isoproterenol induced cardiotoxicity in rats. - S.KAVYA,; M.SATHISH KUMAR, (International Journal of Pharma and Bio Sciences, 2016)
The present study was undertaken to explore the cardioprotective potential of bioflavonoids against isoproterenol induced cardiotoxicity in rats. Cardiotoxicity was induced by isoproterenol (85mg/kg body weight) in animals. Blood biochemical, hematological parameters, urinalysis and histopathological studies were carried to assess the cardio protective effect. Isoproterenol administration induced significant cardiotoxicity in rats, which was evident from enhanced levels of glucose, cholesterol, triglycerides and calcium except sodium. Pretreatment with quercetin (50 mg/kg dose orally) significantly reversed isoproterenol induced cardiotoxicity than the silymarin (50 mg/kg dose orally). From the obtained results it may be concluded that quercetin exerted a significant cardioprotective effect against isoproterenol induced cardiotoxicity in rats than silymarin (p<0.001) for most of the blood biochemical parameters, mean corpuscular hemoglobin count as well as in attenuation of pathological changes in cardiac tissues.